2016
DOI: 10.1128/jvi.00656-16
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis RNA Polymerases IV and V Are Required To Establish H3K9 Methylation, but Not Cytosine Methylation, on Geminivirus Chromatin

Abstract: In plants, RNA-directed DNA methylation (RdDM) employs small RNAs to target enzymes that methylate cytosine residues. Cytosine methylation and dimethylation of histone 3 lysine 9 (H3K9me2) are often linked. Together they condition an epigenetic defense that results in chromatin compaction and transcriptional silencing of transposons and viral chromatin. Canonical RdDM (Pol IV-RdDM), involving RNA polymerases IV and V (Pol IV and Pol V), was believed to be necessary to establish cytosine methylation, which in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 67 publications
4
53
0
Order By: Relevance
“…Isolation of DNA and RNA from symptomatic floral heads and siliques of CaLCuVinfected plants was performed as described previously (36). RNA was reverse transcribed using Super-Script III with oligo(dT) primers, and cDNAs were used to perform quantitative reverse transcriptase PCR (RT-qPCR) with Bio-Rad iQ SYBR green supermix and the Bio-Rad CFX96 real-time PCR detection system (34). PP2A (At1G13320) was used as a reference gene, and comparisons of steady-state host and viral transcript levels were performed using the 2 ϪΔΔCT method (53).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of DNA and RNA from symptomatic floral heads and siliques of CaLCuVinfected plants was performed as described previously (36). RNA was reverse transcribed using Super-Script III with oligo(dT) primers, and cDNAs were used to perform quantitative reverse transcriptase PCR (RT-qPCR) with Bio-Rad iQ SYBR green supermix and the Bio-Rad CFX96 real-time PCR detection system (34). PP2A (At1G13320) was used as a reference gene, and comparisons of steady-state host and viral transcript levels were performed using the 2 ϪΔΔCT method (53).…”
Section: Figmentioning
confidence: 99%
“…The viral chromatin serves as the template for replication and transcription, which depends on host polymerases and associated machineries. In a classic example of host defense and pathogen counterdefense, multiple studies have shown that plants employ DNA and H3K9 methylation to compact and silence geminivirus chromatin, while viral pathogenicity factors inhibit repressive chromatin methylation (27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…To focus solely on the initiation and establishment phases of silencing, and separate these mechanisms from the maintenance of epigenetic marks, investigation has concentrated on transformation or infection of epigenetically naïve (chromatin modification-free) DNA into plants (Greenberg et al, 2011;Bond and Baulcombe, 2015;Jackel et al, 2016). Although transgenesis might be considered an artificial approach to investigate silencing, evidence suggests that transgenesis can occur naturally (Kyndt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Viral DNA methylation was demonstrated to be important for plant defense against geminiviruses. Hypermethylation of the viral genome has been associated with the recovery phenotype in different models of plant-geminivirus interaction [12,14,[34][35][36]. In addition, mutants of RdDM are more susceptible to infection and show an exacerbated symptomatology compared to wild type plants [34].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of viral DNA methylation are associated with symptomatic infection, whereas the host recovery infection phenotypes are related to hypermethylated viral genome, association to repressive histone marks and minichromosomes condensation [14,18,33]. Arabidopsis plants with mutations in components of RdDM pathway are unable to recover after infection with Beet curly top virus lacking a suppressor protein that inhibits methylation (BCTV L2 -), and viral DNA shows hypomethylation [12,[34][35][36]. In natural host-virus interaction, a recovery process also associated with gene silencing was observed in Cucurbit leaf crumple virus-infected watermelon [37].…”
Section: Introductionmentioning
confidence: 99%